DEVELOPMENT OF ASSESSMENT HOTS (HIGHER ORDER THINKING SKILLS) BASED ON PROBLEM SOLVING IN SD/MI - Ulum, Anifa Rosari; Hidayah, Nurul; Yanti, Yuli (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
This research is motivated by the problems that occur, namely students have basically carried out a HOTS-based teaching and learning process or are oriented towards higher-order thinking skills, but during the evaluation process, the measuring instruments or questions used have not been able to measure students' high-level thinking skills. . The type of research to be conducted is Research and Development or R&D (Research and Development). This research refers to the Borg and Gall model which is limited to 7 stages from 10 initial stages, which include potentials and problems, data collection, product design, design validation, design revision, product testing and design revision. The instrument used is in the form of a rating scale to determine the feasibility of the product and to determine the response of educators and students to the feasibility and attractiveness of the product using a Likert scale. Data analysis was carried out, namely collecting data from the validation results of evaluation experts, material experts and language experts, educators and students of SD / MI. HOTS assessment based on problem solving which was developed "Very Feasible or Very Interesting" to be used as a tool for students to train their abilities in higher order thinking. This acquisition was obtained based on product validation by evaluation experts, material experts and linguists. The results of the evaluation from the evaluation expert reached the "Very Appropriate" category with a percentage of 83.84%. The results of the assessment of the material expert received the "Very Appropriate" category with the percentage obtained, namely 88.33%. Whereas in the results of the linguist's assessment the percentage obtained was 87.77% with the category "Very Appropriate".Â